Evaluasi Program Membaca Private Dalam Upaya Peningkatan Kemampuan Membaca Siswa di SD Kusuma Putra - Mutiara Cahyani; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Research on evaluation of private reading program in improving students reading ability at Kusuma Putra elementary school uses the policy evaluation theory by William N. Dunn based on six basic characteristics of evaluation, namely effectiveness, efficiency, adequacy, discretion, responsiveness, and accuracy. The research was conducted at the Kusuma Putra Elementary School, Surabaya City, East Java. The purpose of this study was to find out how the implementation of private reading program by college students of Kampus Mengajar 6 on the student at Kusuma Putra Elementary school. The research method uses a qualitative approach with the type of descriptive research. Data were collected by observation, interview, and literature studies on previous research. The results of the studyindicate that the implementation of private reading has not fully achieved the desired goal due to lack of students awareness of the importance of reading skills.